Effect of Intervention Programs for Improving Maternal Adaptation in Korea: Systematic Review - Hee Sun Kang; Soo Young Yeom; Eun Young Jun (Korean Society of Women Health Nursing, 2013)
PURPOSE: The purpose of this study was to review the literature on intervention for breast cancer survivors and their partners. METHODS: The literature search was performed using MEDLINE, Pubmed, and Proquest to summarize the current state of knowledge regarding intervention for breast cancer survivors and their partners. Articles published between January 2000 and December 2011 were included. RESULTS: A total of 14 studies were identified. Couple-base d intervention was more effective than intervention for survivors alone. Intervention to partners had also effects on their wives. Most studies were conducted in USA with Caucasian women. Sample size of intervention studies was small with most being pilot studies. CONCLUSION: Providing couple-based intervention to breast cancer survivors could have positive impacts on physical, interpersonal, and social aspects in breast cancer survivors. Future studies with large sample and different ethnicity are needed to confirm the effects of couple-based interventions for breast cancer survivors.